Blockchain untuk Keamanan Data Kesehatan dalam Rekam Medis Elektronik - Dina Sonia; Daniel Happy Putra; Mieke Nurmalasari (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2026)
The digital transformation of healthcare through Electronic Medical Records (EMRs) has improved the efficiency and continuity of clinical information management but has also raised significant concerns regarding data security and privacy. The increasing frequency of cyberattacks and the limitations of conventional data protection mechanisms, particularly in developing countries such as Indonesia, highlight the need for more reliable security solutions. This study explores the potential of blockchain technology to enhance EMR security through a Systematic Literature Review (SLR) following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. A total of 13 peer-reviewed articles published within the last five years were systematically reviewed. The findings indicate that blockchain can serve as an additional security layer by improving data integrity and auditability through immutable ledgers, cryptographic hashing, and distributed consensus mechanisms. Data confidentiality is strengthened through patient-centered decentralized access control and advanced cryptographic techniques, while data availability is supported by hybrid architectures using off-chain storage. However, blockchain implementation still faces challenges, including scalability, cryptographic key management, system integration, and regulatory constraints. Overall, blockchain demonstrates strong potential to enhance security and trust within the EMR ecosystem, although it is better positioned as a complementary technology rather than a standalone solution.